Dampak beban, pendapatan, dan beban pokok penjualan terhadap laba usaha dalam isu kenaikan harga minyak dunia pada perusahaan manufaktur sektor basic materials - Baware, Denray; Budiarso, Novi Swandari; Wangkar , Anneke (Manajemen Bisnis dan Keuangan Korporat, 2024)
Operating profit is a measure that assesses how healthy and efficient a company is in conducting its operational activities. This study aims to determine whether there is an effect of operating expenses, operating income, and the cost of goods sold on operating profit amidst the issue of rising global oil prices in basic materials sector manufacturing companies listed on the Indonesia Stock Exchange for the 2022-2023 period. The analytical method used in this thesis is quantitative with an associative approach, which aims to determine the influence and relationships that occur. The data analysis technique in this study uses multiple linear regression. The data processing for this study is conducted using the Jamovi software tool. The results show that there is a significant positive effect of operating expenses and operating income on operating profit, and a significant negative effect of the cost of goods sold on operating profit in basic materials sector manufacturing companies listed on the Indonesia Stock Exchange (IDX) for the 2022-2023 period.